2003
DOI: 10.1161/01.cir.0000060543.64250.80
|View full text |Cite
|
Sign up to set email alerts
|

Twin-Twin Transfusion Syndrome

Abstract: Background-In twin-twin transfusion syndrome (TTTS), the donor and recipient fetus are exposed to differing volume loads and show discordant intertwin vascular compliance in childhood despite identical genotype. We hypothesized that discordance is prevented by intrauterine endoscopic laser ablation of placental anastomoses, which abolishes intertwin transfusion. We tested this by examining pulse wave velocity (PWV) in brachial arteries of twin survivors of TTTS treated with and without laser therapy. Methods a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Persistent pulmonary hypertension after birth has also been described in some recipient twins [109]. Moreover, recipient twins show increased blood pressure levels already in the neonatal period [110,111], while donors have lowered arterial distensibility [112,113], which might be a response to the chronic activation of the renin-angiotensin system. Therefore, further studies to assess the cardiovascular outcome of twin survivors are warranted.…”
Section: Research and Clinical Applications Of Fetal Cardiac Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Persistent pulmonary hypertension after birth has also been described in some recipient twins [109]. Moreover, recipient twins show increased blood pressure levels already in the neonatal period [110,111], while donors have lowered arterial distensibility [112,113], which might be a response to the chronic activation of the renin-angiotensin system. Therefore, further studies to assess the cardiovascular outcome of twin survivors are warranted.…”
Section: Research and Clinical Applications Of Fetal Cardiac Functionmentioning
confidence: 99%
“…However, several studies have also demonstrated that FGR conditions cardiac dysfunction in utero [6,81] that persists postnatally [89], supporting the hypothesis of a primary cardiovascular programming. Apart from FGR, other fetal conditions such as maternal diabetes [69,70], TTTS [113], or in vitro fecundation [138] have also been proposed as prenatal conditionings for fetal cardiovascular programming.…”
Section: Research and Clinical Applications Of Fetal Cardiac Functionmentioning
confidence: 99%
“…Such vascular programming has been shown to be ameliorated, albeit not completely abolished, by intrauterine endoscopic laser ablation of placental anastomoses 64). Even in monozygotic twins without twin-twin transfusion syndrome, the twin with the lower birthweight has been found to have higher systolic blood pressure and pulse pressure in childhood 65)…”
Section: Arterial Stiffening In the Youngmentioning
confidence: 99%
“…Only a few studies have focused on long term vascular consequences of TTTS. Pulse wave velocity, reflecting vascular stiffness, was found to be increased in the brachial artery of donors compared with recipients, a finding suggested to be an effect of fetal arterial remodeling and a risk factor for later hypertension [55,56]. Furthermore, a meta-analysis of pulse wave velocity studies has confirmed that it is predictive for total cardiovascular events [57].…”
Section: Blood Pressure and Vascular Function After Tttsmentioning
confidence: 95%